Monitoring of bone resorption and bone formation in multiple myeloma. - Bacovsky, Jaroslav; Scudla, Vlastimil; Vytrasova, Marketa; Budikova, Marie; Myslivecek, Miroslav (Biomedical papers, 2002)
The article deals with the clinical value of monitoring of serum markers of osteoresorption (ICTP) and bone formation (PICP) in multiple myeloma. In a group of patients treated by conventional chemotherapy and group of patients treated by high dose chemotherapy with autologous peripheral blood stemm cell transplantation (APBSTC).
Keywords: Multiple myeloma / Osteoresorption